ENT 300 : Bumibina Hardware / Asrol Anuar ... [et al.] - Anuar, Asrol; Mustafa, Khairil Masri; Baharin, Muhd Izawan; Shamshull, Mohd Shahril; Basiran, Mohd Izham (2001)
The eompany is fonn as partnership company and starting our business on 1 st January 2003. The scope of the business is to supply construction tools and services related to this business such as painting a house, build a fence and so on. The location chosen by our company to run for the business are base on several reasons such as, the area are fully provided with good basic infrastructure facilities listed as electricity, water, telephone line and transportation linked like PLUS. The business premise also providing a good infrastructure and marvelous condition in order to locate our business tools. Depending on composition worth to 128,8J4 of population in this area, We were expected for a high demand for construction tools and services. The company target market is the contractor and personal user. In addition we would like to be a minor supplier to a major construction project, which run in this area such as PROTON CITY and POLITECNICS. The market share worth RM3.3 million is considered as a big opportunity for our company to take an advantage. On the other hand, we have to challenge a few competitors around the area. But, with a good management in the comp any we were expected to dominate around 8% to 10% of market share within three years.